Pyranone Derivatives With Antitumor Activities, From the Endophytic Fungus Phoma sp. YN02-P-3 - Yu, Chong; Nian, Yin; Chen, Huanhua; Liang, Shuwen; Sun, Mengyang; Pei, Yuehu; Wang, Haifeng (Frontiers in Chemistry, 2022)
Two new pyranone derivatives phomapyrone A (2) and phomapyrone B (3), one new coumarin 11S, 13R-(+)-phomacumarin A (1), three known pyranones (4-6), together with three known amide alkaloids fuscoatramides A-C (7-9), as well as 9S, 11R-(+)-ascosalitoxin (10) were isolated from the endophytic fungus Phoma sp. YN02-P-3, which was isolated from the healthy leaf tissue of a Paulownia tree in Yunnan Province, China. Their structures were elucidated using extensive NMR spectroscopic and HRESIMS data and by comparing the information with literature data. In addition, all compounds were tested for their cytotoxicity activity against human tumor cell lines, the results showed that new compounds 1-3 showed moderate inhibitory activity against HL-60 cell line with IC50 values of 31.02, 34.62 and 27.90 μM, respectively.